Analisis Pengendalian Persediaan Pakan Ternak Ayam Broiler Pada Peternakan Ayam Milik Bapak Weli Tando Dengan Menggunakan Bantuan Alat Analisis POM-QM For Windows - Rosiana; Nurul Hidayat; Jihan Amelia Putri; Putri Adinda (Jurnal Hilirisasi Pengabdian Masyarakat, 2024)
The research objective is to find out how the process of controlling animal feed inventory is implemented by Mr. Weli Tando and implement an inventory management system using the help of the pom-qm for windows analysis tool. This type of research is descriptive with quantitative analysis methods. The data in this study are primary data obtained through direct observation and interviews with Mr. Weli Tando, as well as secondary data collected, the data are in the form of animal feed ordering cost data, animal feed usage data, ordering cost data and storage cost data from Mr. Weli Tando. The results showed that by using the economic order quantity (EOQ) method, Mr. Weli Tando was advised to order 678 sacks of feed per order with a frequency of ordering in a year, with a Safety Stock of 7 sacks with a Reorder Point of 19 sacks so as to save Total Inventory Cost or total inventory cost of Rp 19,034,341.